Aliphatic Biomaker Coal of Seram Island, Maluku Province - Jein Jelsi Lamia; Perry Burhan (IPTEK Journal of Proceedings Series, 2015)
Characteristic of organic geochemistry (biomarker) gives information about environment of coal. Coal was extracted by dichloromethane:methanol (93:7) for 72 h. Extract was obtained then fractionated by its polarity using column chromatography McCharty method. Subsequently, it was extracted to obtain neutral, acid and polar fractions. Neutral fraction was separated by KLTP methode and the extract were fractionated into hydrocarbon component which consist of Aliphatic and Aromatic compounds. The obtaining compounds were characterized by GCMS. Result of GCMS analyzed in Aliphatic fraction shown presence of n-alkane and derivate of terpen.These compounds are considered as important derivatives from natural products of higher plants and some compounds were expected formed by bacteria